A review of Platynaspini (Coleoptera: Coccinellidae) of the Indian subcontinent, including description of a new genus from north-eastern India and Bangladesh - Poorani, J. (Zootaxa, 2023)
The tribe Platynaspini (Coleoptera, Coccinellidae) of the Indian subcontinent is reviewed and ten species of Platynaspis Redtenbacher 1843 are briefly described and illustrated with notes on their distribution, biology, and hosts, wherever known. A lectotype is designated for Platynaspis flavoguttata (Gorham, 1894) (lectotype designation). Neoplatynaspis nataliae gen. et sp. nov. is described and illustrated from the north-eastern Indian state of Meghalaya and Bangladesh. It differs from Platynaspis and Platycrus Szawaryn & Ślipiński 2022, the two existing genera of Platynaspini, by its unusual antenna with a highly modified pedicel, scape and the terminal antennomere forming a large knife-shaped club, legs with enlarged femora, strongly angulate tibiae and trimerous tarsi. A revised key to the genera of Platynaspini and an updated checklist of the Platynaspini of the Indian subcontinent are provided.